Effect of cis-9, trans-11 conjugated linoleic acid (CLA) on the metabolism profile of breast cancer cells determined by H HR-MAS NMR spectroscopy - Maria, Roberta M. (2019)
Conjugated linoleic acid (CLA), a fatty acid found in ruminant food products, has been associated with anticarcinogenic activity. However, its effect on cancer metabolism is unclear. In this paper we evaluated the effects of cis-9, trans-11 CLA on the metabolic profile of MCF-7 and MDA-MB-231 breast cancer cells using high-resolution magic angle spinning (HR-MAS) nuclear magnetic resonance (NMR) spectroscopy. The NMR spectra showed that phosphocholine level, a cancer malignance biomarker, was reduced in both cells treated with CLA, but the reduction was more pronounced in MCF-7 cells. The NMR spectra also showed that CLA has opposite effect on MCF-7 and MDA-MB-231 acetone metabolism. Acetone signal has been observed in the spectra of MDA-MB-231 control cells, but not in the spectra of the cells treated with 50 and 100 µM CLA. Conversely, the acetone signal is very small or not observed in the NMR spectra of MCF-7 control cells and in cells treated with 50 µM of CLA, but is very strong in the spectra of the cells treated with 100 µM of CLA. Therefore, this CLA concentration is causing a ketosis in MCF-7 cells by inducing the use of fatty acids as an energy source or by reducing acetone catabolism. These results indicate that CLA interfere in the metabolism of both cells. However, the strongest effect has been observed on the metabolism of MCF-7 cells cultivated in the presence of 100 µM CLA. Therefore, CLA could be a potential anticarcinogenic drug, especially for cells with positive estrogen receptor, such as MCF-7.